The TF-miRNA Coregulation Network in Oral Lichen Planus. (3rd May 2015) - Zuo, Yu-Ling; Gong, Di-Ping; Li, Bi-Ze; Zhao, Juan; Zhou, Ling-Yue; Shao, Fang-Yang; Jin, Zhao; He, Yuan
Abstract : Oral lichen planus (OLP) is a chronic inflammatory disease that affects oral mucosa, some of which may finally develop into oral squamous cell carcinoma. Therefore, pinpointing the molecular mechanisms underlying the pathogenesis of OLP is important to develop efficient treatments for OLP. Recently, the accumulation of the large amount of omics data, especially transcriptome data, provides opportunities to investigate OLPs from a systematic perspective. In this paper, assuming that the OLP associated genes have functional relationships, we present a new approach to identify OLP related gene modules from gene regulatory networks. In particular, we find that the gene modules regulated by both transcription factors (TFs) and microRNAs (miRNAs) play important roles in the pathogenesis of OLP and many genes in the modules have been reported to be related to OLP in the literature.